1997
DOI: 10.1080/07448489709595582
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Injuries Among University Students in Finland

Abstract: A questionnaire dealing with the incidence of traumatic injuries was sent to 1,000 randomly selected 3rd-year university students in Finland; 617 students responded adequately. Of those, 177 (28.7%) reported a combined total of 281 accidents and 323 separate injuries requiring medical or dental treatment during the preceding 3 years. The accidents resulted in 1,061 days of official sick leave, and one third of the accidents caused permanent sequelae to the affected students. Almost half of all accidents had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
4
12
0
Order By: Relevance
“…Regarding the different type or cause of nonfatal injury in university students, this study found, in agreement with other studies (Sane et al., ; Shi et al., ; Sumilo & Stewart‐Brown, ) that most students had sustained their injuries during sports activities and that the most common causes were falling and traffic‐related injuries. This study finding calls for a need for programs in sport‐injury prevention for university students (Donaldson & Finch, ; Zebas, Loudon, Chapman, Magee, & Bowman, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding the different type or cause of nonfatal injury in university students, this study found, in agreement with other studies (Sane et al., ; Shi et al., ; Sumilo & Stewart‐Brown, ) that most students had sustained their injuries during sports activities and that the most common causes were falling and traffic‐related injuries. This study finding calls for a need for programs in sport‐injury prevention for university students (Donaldson & Finch, ; Zebas, Loudon, Chapman, Magee, & Bowman, ).…”
Section: Discussionsupporting
confidence: 92%
“…There has been a lack of data on nonfatal injury in young adults, including university students, in particular in low‐ and middle‐income countries (Borse & Hyder, ). In studies among university students or youth in the past 12 months injury in high‐income countries found 18% in the United Kingdom (Sumilo & Stewart‐Brown, ), 28.3% in Switzerland (Suris, Jeannin, Michaud, Narring, Diserens, & Smash Group, ), 28.7% (in the past 3 years) in Finland (Sane, Ylipaavalniemi, Turtola, Niemi, & Laaka, ), and 8.8% (in the context of their studies) in Germany (Faller, Mikolajczyk, Akmatov, Meier, & Krämer, ). In low‐ and middle‐income countries, Shi et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prompt and appropriate onsite emergency management is especially important in cases of avulsion (11). It has been estimated that one-third of teeth experiencing TDI get permanent sequelae (12). Pulp necrosis, root resorption and interruption of tooth development in the case of immature teeth are examples of possible complications, which may entail life-long Abstract -Aim: to evaluate the knowledge and awareness of traumatic dental injuries (TDI) in children and adolescents among present and prospective teachers in selected parts of Norway.…”
mentioning
confidence: 99%
“…As a result, TDIs are frequently referred to physicians, dentists and hospital emergency departments without having had appropriate emergency management at the site of the accident (12, 18). The resulting complications can be costly and time‐consuming (19–22) and many teeth are subsequently lost (22), often resulting from a delay in receiving care (12, 18).…”
mentioning
confidence: 99%